Grammar-and-Interlocution: English Articles as Markers of Recipient Role - Douay, Catherine (Revue québécoise de linguistique, 2001)
My core hypothesis is that the article system is directly motivated by a universal communicative problem, which is the necessity of mutual understanding. In the first place I argue, following Gardiner 1932, that a word does not mean per se and that a referent (Gardiner's "thing-meant") can only emerge from the agreement reached by the interlocutors in the referring process. I then suggest that articles play a key role in the process by which referents come to be shared. Their primary function is to determine the interlocutive framework within which the validating process can be achieved. Articles are thus defined as being basically markers of the role assigned to the recipient (β) in the referring process. Detailed examination of contextualized uses supports my analysis. To conclude I suggest that the distinction between different ways of reaching self and other agreement does not only structure the article system but the whole internal organization of the English language.